(untitled) (Raparin Journal of Humanities (RJH), 2024)
The Kurdistan Region is in the stage of economic development in various sectors, and sometimes economic development requires labor. Allowing and bringing foreign labor depends partly on how much the local labor fulfills the needs of the Kurdistan Region, bringing foreign workers sometimes is discussed as critical by the authorities, despite the lack of employment and local labor, but it is allowed to bring foreign labor, foreign workers have a number of social dimensions, which may affect their living conditions. This study aims to determine the living conditions of foreign workers in Erbil. The research method is quantitative method through the use of questionnaire tool, (381) foreign workers in male and female gender were taken as the study’s sample. Then analyzing the data with the use of the program (SPSS), we came to the conclusion that foreign workers in Erbil feel comfortable and safe, cultural differences have not become a problem and obstacle in front of them regarding religion and food, and they quickly adapt to the culture of Kurdistan Region. Foreign workers are more likely to have no social security and have been asked for inappropriate work, The male faces more social, psychological, healthy, economical, and legal problems than the female. Finally, some suggestion and recommendation have been presented to the related parties and the researches that will be done after this research.